Validity and reliability of short-term heart-rate variability from the Polar S810. - Nunan, D; Donovan, G; Jakovljevic, D; Hodges, L; Sandercock, G; Brodie, D (2009)
PURPOSE: : To assess the validity and the reliability of short-term resting heart-rate variability (HRV) measures obtained using the Polar S810 heart-rate monitor and accompanying software. METHODS: : Measures of HRV were obtained from 5-min R to R wave (RR) interval data for 19 males and 14 females during 10 min of quiet rest on three separate occasions at 1-wk intervals using the Polar S810. Criterion measures of HRV were obtained simultaneously using the CardioPerfect (CP; Medical Graphics Corporation, St Paul, MN) 12-lead ECG module. Measures of validity of the Polar S810 were estimated by regression analysis, and measures of reliability of both devices were estimated by analysis of change scores. Measures of the SD of normal-to-normal intervals (SDNN), the root mean square of successive differences (RMSSD), and the low-frequency (LF) and the high-frequency (HF) spectral power and their ratio (LF/HF) were analyzed after log transformation, whereas mean RR and LF and HF in normalized units were analyzed without transformation. RESULTS: : There were marginal differences between the Polar and the CP mean measures of HRV, and the uncertainty in the differences was small. The Polar S810 demonstrated high correlations (0.85-0.99) with CP for all measures of HRV indicating good to near-perfect validity. Except for the low- and the high-frequency normalized units, Polar S810 did not add any substantial technical error to the within-subject variability in the repeated measurements of HRV. CONCLUSION: : HRV measures obtained with the Polar S810 and accompanying software have no appreciable bias or additional random error in comparison with criterion measures, but the measures are inherently unreliable over a 1-wk interval. Reliability of HRV from longer (e.g., 10 min) and/or consecutive 5-min RR recordings needs to be investigated with the Polar and criterion instruments.